Post-Neoliberalism and After: The Relative Center of the Political System and the Rise of the Light Blue Wave in the Mirror of the Foreign Policy of Argentina and Chile - Lorenzini, María Elena; Pereyra Doval, Gisela (Revista de Ciencia Política, 2020)
This article questions the political turns to the left in the first decade of the 21st century and to the right in the second. To do this, we build a political map of South America, applying Coppedge’s (1997, 2000) approach to determine the “relative center of the political system” (rcps). We focus on Argentina’s and Chile’s foreign policy to corroborate the displacements or not of the rcps. We find that both countries gravitated towards the center, indicating an overemphasis on the political turns in recent academic writing. In the most stable political systems, foreign policy did not change, while in those systems that went through diverse cycles, foreign policy changed in varying degrees.